Flexibilización del Derecho del Trabajo y sus implicancias sobre las relaciones laborales en el Perú - Tostes, Marta (2012)
Flexibilization of labor law and its implications on labor relations in PeruThis article discusses the diverse forms of flexibility of labor relations in Peru and analyzes their impact on different types of informality to assess implications of this process in labor relations in Peru. It examinesthese effects taking into consideration information available nationwide in Urban Peru and Metropolitan Lima, for having a historical perspective of the process.It concludes firstly that the informality which is still the main argument for carrying out the flexibilization process didn’t reduce or if it takes in consideration the measurement of informal employment or informal sector of the Peruvian economy. It founds, instead, multiple impacts on the loss of purchasing power of workers in general, affecting fully the functional distribution of income.On the other hand, it notes that the decline process in trade union action has been stopped in recent years and its effectiveness in terms of achieving wage differentials has increased. Recent efforts related to the construction of a decent work agenda and the performance measurement of labor relations policies in this regard it should be reflected in the necessity for early presentation in Congress and approval of the General Labor Law. Finally, it alerts that difficulties for improving working conditions can compromise thevision that people have of democracy and generate political instability.